Bankowość elektroniczna jako kierunek rozwoju usług bankowych - czynniki wpływające na opłacalność zastosowania technologii informacyjnej - Kisielnicki, Jerzy; Wojciechowska-Filipek, Sylwia (E-banking as a direction of banking services development - the factors affecting it application profitabillity, 2005)
This paper answers the following question: Why do the investments in electronic banking not bring the expected returns? This research proves that there are two factors that limit the wide acceptance of electronic banking services: the clients do not trust the IT in electronic banking and are used to traditional forms of banking services. The researchers used the Data Envelopment Analysis (DEA) method to carry out the analysis of banks’ resource utilization. The DEA was further enhanced with surveys sent to clients of selected banks. The research concluds that electronic banking is an attractive development strategy. The benefits however, are not always proportional to the costs. To be competitive, and thus to maintain and increase their business value, banks not only need to develop their electronic services but also improve their overall image of a trustworthy financial institution.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (8); 2005; nr 1094, s. 214-223